2004
DOI: 10.1152/ajpgi.00219.2004
|View full text |Cite
|
Sign up to set email alerts
|

Butyrate specifically modulatesMUCgene expression in intestinal epithelial goblet cells deprived of glucose

Abstract: The mucus layer covering the gastrointestinal mucosa is considered the first line of defense against aggressions arising from the luminal content. It is mainly composed of high molecular weight glycoproteins called mucins. Butyrate, a shortchain fatty acid produced during carbohydrate fermentation, has been shown to increase mucin secretion. The aim of this study was to test 1) whether butyrate regulates the expression of various MUC genes, which are coding for protein backbones of mucins, and 2) whether this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
186
1
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 284 publications
(200 citation statements)
references
References 44 publications
12
186
1
1
Order By: Relevance
“…38,39 The mucus layer covering the colonic mucosa is considered the first line of defence against harmful products arising from the luminal content. 40 Breakdown of mucosal barrier integrity is often observed in diseases such as inflammatory bowel disease which is a documented risk factor for colon cancer. 41 RS through enhanced production of SCFA, particularly butyrate, may be a means by which the colonic mucus barrier is maintained.…”
Section: Discussionmentioning
confidence: 99%
“…38,39 The mucus layer covering the colonic mucosa is considered the first line of defence against harmful products arising from the luminal content. 40 Breakdown of mucosal barrier integrity is often observed in diseases such as inflammatory bowel disease which is a documented risk factor for colon cancer. 41 RS through enhanced production of SCFA, particularly butyrate, may be a means by which the colonic mucus barrier is maintained.…”
Section: Discussionmentioning
confidence: 99%
“…29 (9) SCFAs increase cell metabolism by more than 80% and the production and secretion of mucins by the colon epithelium more than twentyfold 8,29 . Recent research has also demonstrated that shortages of SCFAs greatly reduces the expression of the MUC-2 gene, which is the main agent responsible for transcription of the protein fraction of colon mucins 8,30 . SCF is a cytoprotective agent that has been used for more than three decades in the treatment of several disorders such gastritis, duodenal, stress ulcers, burns, skin lesions, and DII [14][15][16][17][18]32 .…”
Section: Evaluation Of the Application Of Enemas Containing Sucralfatmentioning
confidence: 99%
“…It has been demonstrated that NaB induces differentiation of colon-derived cell lines into mucus-secreting goblet cells that produce mucin glycoproteins and into absorptive enterocytes, which are characterised by elevated ALP activity (Wice et al, 1985;Schroy et al, 1994;Velcich et al, 1995;Gouyer et al, 2001). Induction of differentiation was followed by measurement of ALP activity in cell lysates (Colony and Neutra, 1983) and by RT -PCR detection of mRNA levels of two differentiation markers, CEA (Huitric et al, 1976;Velcich et al, 1995) and mucin 3 (MUC3) (Velcich et al, 1995;Gouyer et al, 2001;Gaudier et al, 2004). In both cell lines, 24 h treatment with NaB resulted in elevation of ALP activity (Figure 2A).…”
Section: Expression Of D-type Cyclins During Induction Of Differentiamentioning
confidence: 99%